Computer game misuse and addiction of adolescents in a clinically referred study sample. (February 2016) - Frölich, Jan; Lehmkuhl, Gerd; Orawa, Helmut; Bromba, Michael; Wolf, Katharina; Görtz-Dorten, Anja
Abstract: Background: Actually it remains unclear whether specific psychiatric disorders, especially emotional disorders and attention deficit hyperactivity disorder (ADHD), may be meaningful in the pathogenesis of computer game misuse. Objective: In this clinical study with adolescent psychiatric patients we expected a moderate to strong correlation between computer game misuse and emotional, conduct and peer problems, as well as symptoms of ADHD. Method: 183 patients (14.9 ± 1.5 years) from a child and adolescent psychiatric clinic were assessed for computer game misuse or addiction using the CSV-S scale in order to distinguish between regular and excessive computer gaming. The Strengths and Difficulties Questionnaire (SDQ) was used to screen for actual emotional and behavioral difficulties. Results: Within the patients' group with problematic computer gaming especially male patients with the highest addiction score spent significantly more time on computer gaming and presented more school performance problems as well as other comorbidities. Excessive gaming correlated significantly with conduct and emotional problems. No specific psychiatric disorders correlated to computer game misuse or addiction. Conclusion: Misuse or addiction of computer games in psychiatric patients seems to be related to an increased rate of conduct and emotional problems but related specific psychiatric diagnoses could not be identified. Highlights: Computer game misuse is related primarily to male adolescents. Computer game addiction is related to diverse conduct and emotional problems. No specific psychiatric disorder is related to computer game addiction.